Farmer Satisfaction Level with Cattle Business Insurance: A Case in South Sulawesi Province, Indonesia - Sitti Nurani Sirajuddin; Hastang Hastang; Agustina Abdullah; Veronica Sri Lestari (International Journal of Agriculture System, 2022)
The Cattle Livestock Business Insurance Program aims to provide protection for cattle from the risk of death and loss of cattle. This study aimed to determine the level of satisfaction of farmers with cattle business insurance in Gowa Regency, South Sulawesi Province. This research was conducted in May 2022. The population is all cattle farmers who follow cattle business insurance in Gowa Regency. The sample is farmers who follow cattle business insurance in Pattalassang sub-district, Gowa Regency amounted 45 people. The research method used was the interview method and FGD (Focus Group of Discussion). The type of data used is qualitative data, namely data in the form of words and quantitative data in the form of numbers or numbers Analysis of the data used with the CSI model. The results show that farmers feel much helped by the existence of AUTS which can minimize the risk of failure in the cattle business, namely the death of the cattle they receive, so that at least it can relieve and not be confused in looking for business capital again. It can also motivate and eliminate the worries of farmers to increase the scale of their business. Farmer satisfaction with AUTS is in the excellent category, which means very satisfied and in accordance with the expectations of farmers, both in terms of service characteristics, personal relationships, service arrangements and customer strength.